Parental Mediation Strategy in the Use of Digital Media in Young Children - Elisha Zakiah Muallimin; Lara Fridani; Nurjannah (International Conferences on Early Childhood Education Proceedings, 2023)
Digital media are now a part of everyday life thanks to the digital revolution. The use of various digital media in early life is expanding in our increasingly digital culture. Early exposure to digital media is seen to be hazardous and requires rigorous parental regulation and supervision. This study examines parental mediation in young children's use of digital media. Researchers examined domestic parental mediation strategies using the literature review methodology. The findings indicated that there are several forms of parental mediation, including co-viewing, active mediation, and restrictive mediation. According to research, a number of variables, including parents' education level, parent-child relationships, ages, socioeconomic status, digital media competence, and parental attitudes of digital media, affect the kind of mediation that parents use.